NIAT DAN PERILAKU WAJIP PAJAK ORANG PRIBADI MENGIKUTI PROGRAM TAX AMNESTY (STUDI FENOMENOLOGI) - Yustina Wahyu Dwijayanti; Hamidah Hamidah (Universitas Jember, 2017)
Tax amnesty is a government program that has the main objective of repatriating Indonesian owned funds stored overseas or owned by Indonesian taxpayers. Researchers use Theory of Planned Behavior as a basis to analyze the intention of the taxpayer in behaving to join the tax amnesty program. Behavioral intent is determined by three determinants of Attitude towards the behavior, subjective norms and perceived behavioral control. Researchers use the phenomenology approach because this method can reflect the direct experience of humans. Researchers will conduct semi-structured interviews to six individual taxpayers attending the tax amnesty program. Respondents in this study include two people taxpayers personally who work as an employee in the field of tax accounting, two people taxpayers personally UMKM, two person taxpayer person as an entrepreneur. Respondents follow this tax amnesty because of the influence of people around such as business partners, tax consultants and officers Tax Office. The results of this study, taxpayers did not report his property as a whole because government is not consistent with the program before the tax amnesty program. In addition, the number of individuals who use the gap and government funds for personal purposes make respondents are reluctant to pay taxes. Keywords: Tax Amnesty, Phenomenology, Theory of Planned Behavior